Pengaruh komitmen guru, kemampuan manajerial, dan peran masyarakat terhadap efektivitas penyelenggaraan pendidikan di sekolah luar biasa (SLB) wilayah kerja I Kabupaten Sleman - MC Rini Rewaniyati (Universitas Sarjanawiyata Tamansiswa, 2015)
The research aims to understand : (1) the influence of teacher’s commitment, principal managerial abilities and the role of public simultaneously on the effectiveness of education at special school in the first work area Sleman regency, (2) the influence of teacher’s commitment on the effectiveness of education at special school in the first work area Sleman regency, (3) the influence of principal managerial abilities on the effectiveness of education at special school in the first work area Sleman regency. (4) the influence of the role of public on the effectiveness of education at special school in the first work area Sleman regency. The population of the research was whole of teachers in the first work area Sleman regency amounting to 100 teachers. Sampling in the study using technique of proportional random sampling of 87 teachers. The data collected by using questionnaires form which had been tested to the 30 teachers and had been qualified for validity by the pearson correlation technique and reliability requirement with alpha’s Cronbach technique. Data analysis techniques used were descriptive analysis, multiple regression and partial correlation, which was preceded by the prerequisite test analysis that was normality test, linearity test, and multicollinearity test. The results of this research show that 1) there is a positive and significant influence of the teacher’s commitment, principals managerial abilities and the role of public on the effectiveness of education at special school in the first work area Sleman regency; 2) there is positive and significant influence of teacher’s commitment partially on the effectiveness of education at special school in the first work area Sleman regency; 3) there is positive and significant influence of principal managerial abilities partially on the effectiveness of education at special school in the first work area Sleman regency, and 4) there is positive and significant influence of the role of public partially on the effectiveness of education at special school in the first work area Sleman Regency. Effective contribution jointly by 68.26%, while the contribution of partially effective: (1) teacher commitment to provide on the effectiveness of education by 20.09% (2) principal managerial abilities to provide the effectiveness of education by 25.50% and (3) the role of public to provide the effectiveness of education by 22.67%.